Analysis of the electrical conductivity and activation energies of bismuth titanate (Bi4Ti3O12) - Carmen Martínez-Morales; Paulina Arellanes-Lozada; Josué López Rodríguez; Antonio Romero-Serrano; D. González-García (Heliyon)
In this study, bismuth titanate (Bi4Ti3O12) was synthesized from pure solid compounds and structurally characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). The electrical properties were evaluated by measuring the electrical conductivity of Bi4Ti3O12 at various oxygen partial pressures (pO2 = 10−5 and 10−8 atm) and temperatures (450 °C-750 °C). The electrical conductivity behavior was assessed during the heating and cooling processes. The material activation energies were determined based on the heating curve, which displayed Arrhenius-type behavior and activation energy slope changes, which could be attributed to point defects. When the temperature was increased from 450 °C to 750 °C at oxygen partial pressures pO2 = 10−5 atm, the electrical conductivity increased by about 62.9 %, whereas when the temperature decreased from 750 °C to 450 °C, the electrical conductivity was reduced by 35.95 %. The electrical behavior of Bi4Ti3O12 was analyzed by establishing its electrical conductivity and chemical activity under different oxygen partial pressures and heating-cooling conditions can allow the synthesis of materials with attractive characteristics for electronic applications.